Interobserver and intermodality agreement of standardized algorithms for non-invasive diagnosis of hepatocellular carcinoma in high-risk patients: CEUS-LI-RADS versus MRI-LI-RADS - Schellhaas, Barbara; Hammon, Matthias; Strobel, Deike; Pfeifer, Lukas; Kielisch, Christian; Görtz, Rüdiger; Janka, Rolf Matthias; Neurath, Markus; Uder, Michael; Seuß, Hannes; Cavallaro, Alexander Josef (European Radiology, 2018)
OBJECTIVES: We compared the interobserver agreement for the recently introduced contrast-enhanced ultrasound (CEUS)-based algorithm CEUS-LI-RADS (Liver Imaging Reporting and Data System) versus the well-established magnetic resonance imaging (MRI)-LI-RADS for non-invasive diagnosis of hepatocellular carcinoma (HCC) in high-risk patients. METHODS: Focal liver lesions in 50 high-risk patients (mean age 66.2 ± 11.8 years; 39 male) were assessed retrospectively with CEUS and MRI. Two independent observers reviewed CEUS and MRI examinations, separately, classifying observations according to CEUS-LI-RADSv.2016 and MRI-LI-RADSv.2014. Interobserver agreement was assessed with Cohen's kappa. RESULTS: Forty-three lesions were HCCs; two were intrahepatic cholangiocarcinomas; five were benign lesions. Arterial phase hyperenhancement was perceived less frequently with CEUS than with MRI (37/50 / 38/50 lesions = 74%/78% [CEUS; observer 1/observer 2] versus 46/50 / 44/50 lesions = 92%/88% [MRI; observer 1/observer 2]). Washout appearance was observed in 34/50 / 20/50 lesions = 68%/40% with CEUS and 31/50 / 31/50 lesions = 62%/62%) with MRI. Interobserver agreement was moderate for arterial hyperenhancement (ĸ = 0.511/0.565 [CEUS/MRI]) and "washout" (ĸ = 0.490/0.582 [CEUS/MRI]), fair for CEUS-LI-RADS category (ĸ = 0.309) and substantial for MRI-LI-RADS category (ĸ = 0.609). Intermodality agreement was fair for arterial hyperenhancement (ĸ = 0.329), slight to fair for "washout" (ĸ = 0.202) and LI-RADS category (ĸ = 0.218) CONCLUSION: Interobserver agreement is substantial for MRI-LI-RADS and only fair for CEUS-LI-RADS. This is mostly because interobserver agreement in the perception of washout appearance is better in MRI than in CEUS. Further refinement of the LI-RADS algorithms and increasing education and practice may be necessary to improve the concordance between CEUS and MRI for the final LI-RADS categorization. KEY POINTS: • CEUS-LI-RADS and MRI-LIRADS enable standardized non-invasive diagnosis of HCC in high-risk patients. • With CEUS, interobserver agreement is better for arterial hyperenhancement than for "washout". • Interobserver agreement for major features is moderate for both CEUS and MRI. • Interobserver agreement for LI-RADS category is substantial for MRI, and fair for CEUS. • Interobserver-agreement for CEUS-LI-RADS will presumably improve with ongoing use of the algorithm.
EVALuna2:34689